Pengaruh Celebrity Endorser, Brand Image, dan Kepercayaan Konsumen terhadap Keputusan Pembelian Sepeda Motor Honda Vario di Kota Denpasar - Lini, Annis Kiswa; Nurcahya, I Ketut (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
ABSTRACT The development of information technology can lead consumers to quickly find out information about the existence of a product. Companies are required to provide information about their products correctly so it gets a positive response from consumers. Marketing strategies do companies is to provide information to consumers through advertising. By using celebity endorsers in advertising is expected to attract the attention of consumers and increase awareness of products. The purpose of this study was to determine the effect of celebrity endorser, brand image, and consumer confidence in the purchase decision. The results based on multiple linear regression analysis showed that the celebrity endorser, brand image, and consumer confidence positive and significant impact on purchasing decisions. Keywords: celebrity endorser, brand image, consumer confidence, purchasing decisions